“Wounds are eloquent”: Trauma and Alterities in El ruido de las cosas al caer of Juan Gabriel Vásquez - Miranda-Recinos, Gabriela (2026)
This article examines the wound and subsequent trauma suffered by the protagonist Antonio Yammara in the novel El ruido de las cosas al caer by Colombian writer Juan Gabriel Vásquez. In this novel, the belated experience of trauma responds to theoretical and methodological tendencies identified in literary trauma studies. In this instance, the violent social context will provide guidelines for understanding trauma at the emotional, perceptual, and somatic level. In the diegesis, the desire to evoke the forgotten and repressed arises from the extrapolation of two events, two historical presents and two spaces, which function based on a catalyst: the media tragedy of the dismembered hippopotamus in 2009. This event displays the memory of the initial trauma. In a second instance, the moment associated with the wound suffered by the character invites a duplicative mechanism, which operates as the recurring warning that emanates from the wound, one that warns a condition of alterity. This effect of the double in the novel, the exchange of lives, insinuated in the diegesis, allows the identification and deciphering of the various levels of the violent and traumatic crisis suffered by the character Yammara.